Progreso del mecanismo de desarrollo limpio. desafío entre inversión económica y cooperación - Meiattini, Silvia (M+A. Revista Electrónica de Medioambiente, 2009)
The purpose of this study is to explore the most interesting and controversial mechanism of the Kyoto Protocol, the CDM, which, taking charge of the conflict between efficiency and equity and fairness, gives the Parties the opportunity to meet their quantified targets in the most economically efficient way and to contribute to the cause of sustainable development in developing countries. The actions directed toward both goals are analyzed, considering in particular the technologies which have been employed and where, the possible benefits and obstacles; all the information has been taken from articles recently published in specialized journals, data provided by the UNFCCC and the Institute Risø. It is evident the indisputable value of the more efficient projects in mitigation, but the main results indicate the need of promoting specialized education in host countries and strengthening the mechanism to ensure sustainable development oriented projects.
Keywords: Mitigation; Clean Development Mechanism; Development Cooperation